1996
DOI: 10.1055/s-2007-999029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study on a Novel Inhibitor of Thrombin Containing No Side Chain at the P1 Position of the Polypeptide Chain

Abstract: The presented work allows one to speculate that the hydrophobic contacts of the residues located at the P2 and P3 positions with the corresponding subsites of thrombin (S2 and S3) allow the synthesis of compounds that can react with thrombin specifically and probably may not interact with other trypsin-like serine proteases. Substitution of proline by m-Abz-residue may result in the development of novel substrates and inhibitors for thrombin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Their freeenergy simulations showed that the proline-glycine flip requires very little energy, less than 3 kCal per mol, and that there were no steric hindrances to prevent the proline-glycine flip from occurring. The possibility of binding to a specific molecule that induces a conformational change leading to toxin activation had been proposed before (112); this event is not novel, since thrombin (98,99) and the hepatitis C virus NS3 protease also demonstrate such a phenomenon (130). However, the highly charged N-terminal region of the toxins have significant sequence homology to that of trypsinogen.…”
Section: Putative Mechanism Of Actionmentioning
confidence: 99%
“…Their freeenergy simulations showed that the proline-glycine flip requires very little energy, less than 3 kCal per mol, and that there were no steric hindrances to prevent the proline-glycine flip from occurring. The possibility of binding to a specific molecule that induces a conformational change leading to toxin activation had been proposed before (112); this event is not novel, since thrombin (98,99) and the hepatitis C virus NS3 protease also demonstrate such a phenomenon (130). However, the highly charged N-terminal region of the toxins have significant sequence homology to that of trypsinogen.…”
Section: Putative Mechanism Of Actionmentioning
confidence: 99%